2008
DOI: 10.1088/0957-4484/19/37/375103
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular uptake, trafficking and subcellular distribution of folate conjugated single walled carbon nanotubes within living cells

Abstract: Herein we studied the uptake, trafficking and distribution of folate conjugated single walled carbon nanotubes (SWNTs) within living cells. SWNTs were noncovalently functionalized with chitosan and then linked with folate acid and fluorescence dye Alexa Fluor 488 (denoted FA-SWNTs). Hep G2 cells were cultured in vitro and incubated with FA-SWNTs at different levels. The FA-SWNTs exhibited a concentration-dependent uptake within Hep G2 cells, and Hep G2 cells were able to internalize FA-SWNTs via a folate recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 32 publications
3
41
1
2
Order By: Relevance
“…However, it is notable that the conjugation of folic acid on MWCNTs enabled them to enter cells, indicating that specific, receptor-mediated endocytosis allows large fibers to be internalized. (38)(39)(40)(41)(42) We recently showed that MWCNTs coated with albumin on their surface were not endocytosed by two different human mesothelial cell lines. (17) Instead, we found that these MWCNTs directly pierced through the plasma and nuclear membranes in a diam- (43) showed that MWCNTs coated with both albumin and phospholipid (DPPC, dipalmitoyl-phosphatidylcholine) were successfully internalized by bronchial epithelial BEAS-2B cells.…”
Section: Size and Surface Characteristics Of Carbon Nanotubes Determimentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is notable that the conjugation of folic acid on MWCNTs enabled them to enter cells, indicating that specific, receptor-mediated endocytosis allows large fibers to be internalized. (38)(39)(40)(41)(42) We recently showed that MWCNTs coated with albumin on their surface were not endocytosed by two different human mesothelial cell lines. (17) Instead, we found that these MWCNTs directly pierced through the plasma and nuclear membranes in a diam- (43) showed that MWCNTs coated with both albumin and phospholipid (DPPC, dipalmitoyl-phosphatidylcholine) were successfully internalized by bronchial epithelial BEAS-2B cells.…”
Section: Size and Surface Characteristics Of Carbon Nanotubes Determimentioning
confidence: 99%
“…For instance, oxidized nanotubes are more likely to enter cells via endocytosis with the help of specific ligands (42,46,(49)(50)(51)(52) because the oxidation of nanotubes introduces carboxyl groups, which provides a negative charge to their surface, resulting in repulsion from the plasma membrane unless the carbon nanotube has ligands that are recognized with a high affinity by the cell. Many ligands (folic acid, (42) albumin (46) and epidermal growth factor (49) ) have been reported to facilitate uptake by specific cell types. Alternatively, a carbon nanotube with amino groups presents a positive charge on its surface and can enter cells via energy-independent piercing and diffusion.…”
Section: Size and Surface Characteristics Of Carbon Nanotubes Determimentioning
confidence: 99%
“…A n o t h e r f r e q u e n t l y -s t u d i e d n o n -c o v a l e n t interaction is a targeted drug delivery system based on polysaccharide [sodium alginate (ALG) and chitosan (CHI)] modified carboxylate SWCNTs for controlled release of DOX; in addition, including folic acid as a targeting agent [130]. The CHI/ALG-SWCNTs were initially oxidized and cut and then the appropriate polysaccharide (ALG or CHI), leading to the encapsulation of the SWCNTs by the polysaccharides [129][130][131][132].…”
Section: Non-covalent Methodsmentioning
confidence: 99%
“…Moreover, SWCNTs have been shown to enter mammalian cells Chin et al, 2007;Kam et al, 2004;Kostarelos et al, 2007) and due to their promising properties, SWCNT-based materials have already been investigated as potential delivery vehicles for intracellular transport of nucleic acids Pantarotto et al, 2004), proteins (Kam et al, 2004; and drug molecules Chen et al, 2008;. SWCNTs have been functionalized with antibodies and low-molecular-weight targeting agents, providing high efficiency for nanotube internalization into cells Bottini et al, 2006;Cato et al, 2008, Singh et al, 2005Kang et al, 2008;Shao et al, 2007;Welsher et al, 2008;Zeineldin et al, 2009).These systems also have higher loading capacity and allow for the incorporation of targeting agents and stealth molecules may also be added to evade the immune system. (Mu et al, 2009;Heister et al,2009) Such systems have been loaded with drug molecules such as doxorubicin (DOX) via p-p stacking interactions, methotrexate, Paclitaxel and quercetin.…”
Section: Carbon Nanotubes and Their Impor-tance In Anticancer Drug Dementioning
confidence: 99%